2023
DOI: 10.3390/ejihpe13090128
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia (No Mobile Phone Phobia) and Psychological Health Issues among Young Adult Students

Nasrin Abdoli,
Dena Sadeghi-Bahmani,
Nader Salari
et al.

Abstract: Background: Smart phone use has become a part of people’s everyday life. However, when the lack of using the smart phone to establish and maintain electronic communication is related to psychological distress, such a behavior may be considered a modern-age phobia, or nomophobia (no mobile phone phobia). The aims of the present study were to investigate among a sample of young adults the associations between scores for nomophobia and symptoms of depression, anxiety, stress, insomnia, and obsessive–compulsive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…A study in Lebanon found that while higher anxiety and insomnia were significantly associated with severe nomophobia, nomophobia was unrelated to insomnia [13]. Another study on young adults found that nomophobia was associated with symptoms of anxiety although it was unrelated to insomnia [14].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Lebanon found that while higher anxiety and insomnia were significantly associated with severe nomophobia, nomophobia was unrelated to insomnia [13]. Another study on young adults found that nomophobia was associated with symptoms of anxiety although it was unrelated to insomnia [14].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research has suggested that despite the overlap in the reasons for quitting smoking and/or vaping, there are unique barriers and facilitators to vaping cessation among YA [ 10 ], resulting in a gap in the evidence for how best to engage YA EC users in effective cessation resources [ 8 ]. Despite heavy cell phone use and dependence [ 12 ], some data have suggested that the majority of YAs (90%) prefer not to talk on the phone [ 13 ], which has raised questions whether this age group would engage with cessation treatment that requires a one-on-one voice connection with a quitline coach.…”
Section: Introductionmentioning
confidence: 99%